Use of expanded Neisseria meningitidis serogroup B panels with the serum bactericidal antibody assay for the evaluation of meningococcal B vaccine effectiveness - Ray Borrow; Federico Martinón-Torres; Véronique Abitbol; Anar Andani; Scott Preiss; Alessandro Muzzi; Laura Serino; Woo-Yun Sohn (Taylor & Francis Group, 2023)
Introduction Neisseria meningitidis serogroup B (NmB) antigens are inherently diverse with variable expression among strains. Prediction of meningococcal B (MenB) vaccine effectiveness therefore requires an assay suitable for use against large panels of epidemiologically representative disease-causing NmB strains. Traditional serum bactericidal antibody assay using exogenous human complement (hSBA) is limited to the quantification of MenB vaccine immunogenicity on a small number of indicator strains. Areas covered Additional and complementary methods for assessing strain coverage developed previously include the Meningococcal Antigen Typing System (MATS), Meningococcal Antigen Surface Expression (MEASURE) assay, and genotyping approaches, but these do not estimate vaccine effectiveness. We provide a narrative review of these methods, highlighting a more recent approach involving the hSBA assay in conjunction with expanded NmB strain panels: hSBA assay using endogenous complement in each vaccinated person's serum (enc-hSBA) against a 110-strain NmB panel and the traditional hSBA assay against 14 (4 + 10) NmB strains. Expert opinion The enc-hSBA is a highly standardized, robust method that can be used in clinical trials to measure the immunological effectiveness of MenB vaccines under conditions that mimic real-world settings as closely as possible, through the use of endogenous complement and a diverse, epidemiologically representative panel of NmB strains.